Modeling the effect of process parameters on the photocatalytic degradation of organic pollutants using artificial neural networks - Ayodele B.V.; Alsaffar M.A.; Mustapa S.I.; Cheng C.K.; Witoon T. (Institution of Chemical Engineers, 2023)
Antibiotics; Azo dyes; Biodegradation; Network architecture; Neural networks; Phenols; Sensitivity analysis; Styrene; Hydrothermal temperature; Initial concentration; Levenberg-Marquardt; Mean absolute error; Modelling techniques; Phenol concentration; Photo catalytic degradation; Photocatalyst concentration; Organic pollutants